Improving Islamic Religious Education Learning Activities Through The Talking Stick Learning Model - Mochammad Syafiuddin Shobirin; Nisa' Atus Salamah (SCHOOLAR: Social and Literature Study in Education, 2022)
The implementation of the Talking stick learning model in Islamic Religious Education learning itself can make students more active in speaking. The purposes of this research are 1) Implementing the Talking Stick learning model at MA Al-Bairuny Jombang 2) How is the activity of students in class X at MA Al-Bairuny Jombang when the Talking Stick learning model is applied, and 3) how is the student response to one of the class X at MA Al Bairuny on moral learning with the Talking Stick model. This research is a qualitative research. And the object used in this research is one of class X students at MA Al-Bairuny. The data collection method used is the observation method, the interview method, and the documentation method. The finding was that at MA Al-Bairuny the Talking stick learning method had not been applied to Islamic Religious Education education, and after it was applied to one of the X grades at MA Al Bairuny, the activity increased although not significantly.